The impact of human resource management (HRM) practices on labour productivity in libyan national oil corpration: the mediating role of social skills - Mohamed Abulkasim, Mohamed Ibrahim (Universiti Sains Islam Malaysia, 2024)
There is an agreement among researchers on the relationship between Human Resource Management (HRM) practices and improving labour productivity. HRM practices greatly influence organisational objectives. Lack of HRM practices and low labour competency necessitate investigating the labour productivity of Libyan oil producing companies. It has become obvious that the effect of HRM on labour productivity largely depends on social skills. However, many previous studies ignored the role of social skills as a mediator between HRM and labour productivity. Thus, the present study investigates the relationship of Human Resource Management practices (e.g. staffing, on-the-job training, decentralised decisions, and employee motivation) and labour productivity. The study explores the mediating role of social skills between HRM and labour productivity on Libyan oil and gas companies that play an important role in Libya‘s economic development. The data of this study were collected using the survey approach, Questionnaires were administered to 600 randomly selected respondents, 378 respondents returned the questionnaires and 339 usable questionnaires make up the response rate of 89.6% . The findings indicated that there is direct relationship between HRM practices and labour productivity. In addition, the present study supported the hypothetical relationship proposed in the theoretical framework revealing that social skills play a mediating role on improving the relationship between HRM practices and labour productivity. Thus, with the appropriate usage of social skills, employees are able to contribute toward enhancing labour productivity. Moreover, the findings revealed that collaboration and networking skills are important components contributing to the theoretical and practical knowledge in the field of HRM Practices. The findings implied that the oil and gas industry must concentrate on the key antecedents of HRM including collaboration and networking skills in pursuit of increased long-term productivity and turnover. Finally, the role of staffing and on-the-job training as HRM practices contradict the results of previous studies that found these factors to be crucial for labour productivity. Thus, such relationships need to be further explored and investigated.